Management Information System for Monitoring and Inspection of the Implementation of Universities - Gerit John Rupilele, Frits; Soulis, Irwan; Palilu, Aram; Hasibuan, Abdurrozzaq; Fransisca Winesty Tutupary, Ontje; Alfret Goraph, Frets; Sidete, Herman; Mouw, Erland; Laritmas, Selfianus; Tondo, Simson; Jamil, Mohamad; Dara Utama, Mutiara; et al. (International Journal of Engineering and Technology, 2018)
Inspection of Universities infringement (PT) is one of Controlling, Supervising and Guidance (dalwasbin) activities aimed at developing problematic universities in order to be back on track and able to run Tri Dharma of Higher Education in accordance with National Standard of Higher Education. Based on the results of evaluation and inspection of Higher Education in 2017 at Coordination of Private Higher Education Region XIV there found 29 Universities out of 61 Universities that committed violations. Management of infringement inspection of Higher Education requires the role of information technology due to the geographic area of the Higher Education and management of Higher Education inspection that is still manual causing management to be ineffective and inefficient.Â Coordination of Private Higher Education Region XIV requires an information system that can support and assist data of infringement in universities and management of universities inspection. The design of information system in this research used waterfall method. The design of system models used unified modeling language diagrams (UML) including use case diagrams and activity diagrams. The design of this information system generated a system that can support the management of integrated and centralized infringement inspection to facilitate the inspection, monitoring and reporting of inputs and information for Coordination of Private Higher Education and the ministry in mapping the institutional quality Higher Education. Â Â